2016
DOI: 10.1177/0022146516667534
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border Ties as Sources of Risk and Resilience

Abstract: Few studies have examined the associations between health and the cross-border ties that migrants maintain with their family members in communities of origin. We draw on theory related to social ties, ethnic identity, and mental health to examine cross-border ties as potential moderators of the association between migration-related stress and psychological distress among Latino migrants. Using data from the National Latino and Asian American Survey, we find that remittance sending is associated with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Nevertheless, a small but increasing body of literature exists, which examines and theorises about the implications of transnational ties for migrants' well-being. This set of studies comprises mainly quantitative (Afulani, Torres, Sudhinaraset, & Asunka, 2016;Alcántara et al, 2015;Murphy & Mahalingam, 2004;Torres, Alcántara, et al, 2016) but also a few qualitative (Viruell-Fuentes, 2006;Viruell-Fuentes & Schulz, 2009) contributions.…”
Section: Transnational Ties and Migrants' Well-being: Empirical Andmentioning
confidence: 99%
“…Nevertheless, a small but increasing body of literature exists, which examines and theorises about the implications of transnational ties for migrants' well-being. This set of studies comprises mainly quantitative (Afulani, Torres, Sudhinaraset, & Asunka, 2016;Alcántara et al, 2015;Murphy & Mahalingam, 2004;Torres, Alcántara, et al, 2016) but also a few qualitative (Viruell-Fuentes, 2006;Viruell-Fuentes & Schulz, 2009) contributions.…”
Section: Transnational Ties and Migrants' Well-being: Empirical Andmentioning
confidence: 99%
“…Within the transnationalism framework, cross-border ties are defined as the social connections maintained with close kin in countries-of-origin that, not only include physical contact (such as visits), but may also include financial and cultural aspects of transnationalism. 1 Scholars have found evidence that cross-border contact with family and friends living in countries of origin is significantly associated with mental health and overall wellbeing among immigrant populations in the US (Alcántara, Molina, et al, 2015; Samari, 2016; Torres, Alcántara, et al, 2016). While we are not aware of any empirical work examining the relationship between cross-border ties and alcohol use, some work has found a relationship between cross-border ties and other health outcomes including self-rated health (Afulani, Torres, Sudhinaraset, & Asunka, 2016; Torres, 2013), and health behaviors such as smoking (Alcántara, Molina, et al, 2015) as well as self-reported body mass index (Gorman & Novoa, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A transnational framework highlights immigrants'cross-border ties, or contact with family and friends in their country of origin through long-distance communication, remittance-sending, political participation and return visits (Faist, Bilecen, Barglowski, & Sienkiewicz, 2015; Falicov, 2007; Waldinger, 2015). Scholars have begun to develop theory outlining hypothetical cultural and psychological pathways by which these transnational connections may impact health and health behaviors, as well as test the associations between ongoing cross-border connection and these outcomes (Alcántara, Chen, & Alegría, 2015; Alcántara, Molina, & Kawachi, 2015; Gorman & Novoa, 2016; Samari, 2016; Torres, Alcántara, Rudolph, & Viruell-Fuentes, 2016; Torres, Lee, González, Garcia, & Haan, 2016).…”
mentioning
confidence: 99%
“…An emerging body of literature that analyzes the impact of transnational ties on migrant mental health indicates that such ties can be both a source of risk and of resilience ( Torres, Alcántara, Rudolph, & Viruell-Fuentes, 2016 ). To date, most researches on these issues come from the US among Latino migrants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have achieved mixed results regarding the impact of cross-border family separation on mental health. A study on Latino migrants in the US found no association between migration-related family stress defined as feeling guilty regarding leaving and having limited contact with family and friends in the country of origin ( Torres, Alcántara, et al, 2016 ). However, among Mexican immigrant mothers, separation from children and spouses has been shown to contribute to depression ( Ornelas & Perreira, 2011 ).…”
Section: Introductionmentioning
confidence: 99%